Muzyka jako droga do samookreślenia w wielokutlurowym świecie - Karolina Golemo (Ksiegarnia Akademicka Publishing, 2021)
The Cape‑Verdean community is one of the most traditional and most important immigrant groups in Portugal. Since the first arrivals to the Portuguese land, the Cape‑Verdean people have settled in the Lisbon area. The cabo‑verdianos community actively participate in the artistic milieu of the multicultural Portuguese capital. Music has always been considered as one of the most relevant mechanisms of transmission of the Cape‑Verdean identity. The multiplicity of musical forms present both in the archipelago territory and in the Diaspora environment is a real proof of the creolization of the Cape‑Verdean culture. This paper aims to describe the interdependence between the musical creation of Cape‑Verdean immigrants (and especially the young Portuguese of Cape‑Verdean origins) and their searching for, re‑interpreting and defining the own cultural identity.